The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.ces.2019.03.015
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of power and flow characteristics between batch and in-line rotor-stator mixers

Abstract: Rotor-stator mixers are used in many industries to perform emulsification and de-agglomeration processes. Despite previous research, different modes of operation have not been compared in terms of flow and power characteristics. The aim of this study was to use CFD to investigate power and flow characteristics of a Silverson L5M mixer operating in batch and in-line mode.MRF was used along with the standard k − turbulence model for the simulations. Results suggest that batch mixers can be characterised in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…This relationship, being linear and with a non‐zero intercept, has not been incorporated into any other predictions of the power number in stirred vessels. The same relationship has been found for both in‐line 23–25 and batch 26,27 rotor‐stator mixers operating in the fully turbulent regime. Interestingly it was found that when changing between batch and in‐line mode in a rotor‐stator mixer, not only is the relationship between the flow number and the power number the same form, but the empirical constants are also the same.…”
Section: Introductionsupporting
confidence: 75%
“…This relationship, being linear and with a non‐zero intercept, has not been incorporated into any other predictions of the power number in stirred vessels. The same relationship has been found for both in‐line 23–25 and batch 26,27 rotor‐stator mixers operating in the fully turbulent regime. Interestingly it was found that when changing between batch and in‐line mode in a rotor‐stator mixer, not only is the relationship between the flow number and the power number the same form, but the empirical constants are also the same.…”
Section: Introductionsupporting
confidence: 75%
“…For the purpose of revealing the effects of the operating parameters and structural parameters on the emulsification performance, the flow field is numerically studied using ANSYS Fluent. The multiple reference frames (MRF) model is adapted when solving the momentum equations for the entire domain; that is, a rotating frame is used for the region containing the rotor while a stationary frame is used for other regions of the domain, as shown in Figure . Grids are generated in ANSYS Meshing to achieve the discretization of the computational domain and are further refined based on the velocity gradient .…”
Section: Methodsmentioning
confidence: 99%
“…The power consumption P of the high shear mixer can be calculated from eq , where N is the rotor speed and M is the torque of the mixer. ,,, Subsequently, ε̅ of the mixer can be calculated by eq , where ρ M is the density of the mixture and V is the volume of the fluid in the mixing chamber . The detailed liquid–liquid two-phase CFD modeling methods are shown in Appendix III in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…The power consumption was calculated by the torque on the rotor in this work, which is shown in eq . , CFD simulation method is widely applied to evaluate the torque on the rotor in HSMs. John et al validated the CFD simulation method to predict the power consumption by experimental measurements in both inline and batch HSMs. where N denotes the rotor speed and M represents the torque on the rotor.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…37,38 CFD simulation method is widely applied to evaluate the torque on the rotor in HSMs. 39−42 John et al 40 validated the CFD simulation method to predict the power consumption by experimental measurements in both inline and batch HSMs.…”
Section: Apparatusmentioning
confidence: 99%